Heat transfer optimization using RSM for hybrid nanofluid flow impinging obliquely on a permeable shrinking sheet - Yahaya, Rusya Iryanti; Mustafa, Mohd Shafie; Md Arifin, Norihan; Pop, Ioan; Md Ali, Fadzilah; Mohamed Isa, Siti Suzilliana Putri (Penerbit Akademia Baru, 2025)
Fluid flow may strike a surface at an angle due to the physical limitations of the nozzle or contouring of the surface. The heat transfer optimization for the Al2O3-Cu/water hybrid nanofluid flow impinging obliquely on a permeable shrinking sheet is analyzed in this study. Flow over a shrinking sheet may occur during polymer and metal sheet extraction, wire drawing, and glass-fiber production. The first step in this study involves reducing the governing partial differential equations and boundary conditions into non-linear ordinary differential equations via similarity transformation. Subsequently, these equations are solved using built-in finite difference code in MATLAB bvp4c solver. It is found that the increment of the suction parameter enhances the heat transfer rate represented by the physical quantity of interest called the local Nusselt number. However, the opposite occurs when the nanoparticle volume fraction of Cu and the magnitude of the shrinking parameter increase. Meanwhile, the normal and shear components of skin friction are augmented by the rise in the suction parameter and nanoparticle volume fraction of Cu. Then, the statistical analysis and optimization done using the response surface methodology (RSM) revealed that the local Nusselt number (Reϰ−1/2Nuϰ) is highly impacted by the suction parameter (S), followed by the shrinking parameter (λ) and nanoparticle volume fraction of Cu (Φcu). The maximum value of Reϰ−1/2Nuϰ is approximated to be 13.30539 when the magnitude of S is at the highest, while |λ| and Φcu are at the lowest (i.e., S = 2.2, λ = −0.8, and Φcu = 0.01).